2016
DOI: 10.21037/jtd.2016.03.96
|View full text |Cite
|
Sign up to set email alerts
|

High concordance of ALK rearrangement between primary tumor and paired metastatic lymph node in patients with lung adenocarcinoma

Abstract: Background: Lung cancer has heterogeneous features. It remains unclear whether ALK rearrangement was distributed heterogeneously in tumor from different anatomic sites. To address this issue, we investigate the concordance of ALK rearrangement between primary tumors and paired metastatic lymph nodes in pulmonary adenocarcinoma patients. Results: A total of 101 patients were enrolled into this study with a median age of 60 years old (range, 35-78 years). ALK rearrangement was found in 20 primary lesions, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…However, the possibility of a low protein expression of the rearranged transcript, the fact that ALK rearrangement leads to a non‐translated transcript or, as mentioned above, the fact that we used archival tissue, may also be considered as an alternative explanation for the ALK IHC false‐negative cases. Similar to the study by Hou et al ., in our study ALK IHC showed a high concordance of 94% between primary tumour and matched metastases . This result is in agreement with other reports suggesting strongly that ALK IHC can be used as a screening test …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the possibility of a low protein expression of the rearranged transcript, the fact that ALK rearrangement leads to a non‐translated transcript or, as mentioned above, the fact that we used archival tissue, may also be considered as an alternative explanation for the ALK IHC false‐negative cases. Similar to the study by Hou et al ., in our study ALK IHC showed a high concordance of 94% between primary tumour and matched metastases . This result is in agreement with other reports suggesting strongly that ALK IHC can be used as a screening test …”
Section: Discussionsupporting
confidence: 94%
“…However, recent studies using the next‐generation sequencing (NGS) approach mainly over‐ruled the concept of oncogenic somatic mutations heterogeneity, and attributed the previous observations to different testing methods and sampling issues . Conversely, similar studies looking into gene rearrangements are uncommon . As the majority of lung adenocarcinomas are diagnosed at an advanced stage with evidence of metastasis, the question remains as to whether the primary or the metastatic tumour should be submitted for molecular studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al . explored the status of ALK rearrangements between primary tumors and paired metastatic lymph nodes in 101 patients with lung adenocarcinomas . The concordance rate of ALK rearrangements between primary tumors and paired metastatic lymph nodes was 98%.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the ALK gene in 78 paired specimens (primary tumor site and paired metastatic lymph nodes); 98.7% of the patients had concordant ALK rearrangements . However, these studies did not further analyze the histological classification between primary and metastatic lymph nodes . Few reports have simultaneously explored the intra‐tumor heterogeneity in histomorphology and molecular subtype between primary and paired metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%